2015
DOI: 10.3758/s13414-015-0975-5
|View full text |Cite
|
Sign up to set email alerts
|

Watching a real moving object expands tactile duration: The role of task-irrelevant action context for subjective time

Abstract: Although it is well established that action contexts can expand the perceived durations of action-related events, whether action contexts also impact the subjective duration of events unrelated to the action remains an open issue. Here we examined how the automatic implicit reactions induced by viewing task-irrelevant, real moving objects influence tactile duration judgments. Participants were asked to make temporal bisection judgments of a tactile event while seeing a potentially catchable swinging ball. Appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 58 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…In this sense, an action-related dilation of time in the present study might be somewhat surprising, because visual features of our target stimulus (white disk) was not directly associated with actions (release and repress movements of a key). Recent studies, however, indicated that action can affect perception of a stimulus even when that stimulus was irrelevant to a motor task (Jia, Shi, Zang, & Muller, 2015;Tomassini, Spinelli, Jacono, Sandini, & Morrone, 2015). For example, preparation of reaching movements to a bar modulated a contrast sensitivity to a visual stimulus (Gabor patch) totally unrelated to the movements (Tomassini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, an action-related dilation of time in the present study might be somewhat surprising, because visual features of our target stimulus (white disk) was not directly associated with actions (release and repress movements of a key). Recent studies, however, indicated that action can affect perception of a stimulus even when that stimulus was irrelevant to a motor task (Jia, Shi, Zang, & Muller, 2015;Tomassini, Spinelli, Jacono, Sandini, & Morrone, 2015). For example, preparation of reaching movements to a bar modulated a contrast sensitivity to a visual stimulus (Gabor patch) totally unrelated to the movements (Tomassini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…But such subjective duration expansion diminished when their imitation of the facial expressions was inhibited by holding a pen between their lips ( Effron et al, 2006 ). A recent study ( Jia et al, 2015 ) has also demonstrated that possibility of stimulus–response interaction could change perceived duration of a tactile stimulus.…”
Section: Introductionmentioning
confidence: 96%
“…Not only spatial perception, time perception can also be better understood within the framework of embodiment ( Clark, 1999 ; Droit-Volet et al, 2013 ; Wittmann, 2013 ; Maniadakis et al, 2014 ). Studies have demonstrated that bodily states markedly influence time perception ( Yarrow et al, 2001 ; Droit-Volet and Gil, 2009 ; Hagura et al, 2012 ; Shi et al, 2013 ; Jia et al, 2015 ). For example, external trains of clicks and intake of drugs (e.g., amphetamine) can change bodily arousal levels, leading to distortions of perceived durations ( Maricq et al, 1981 ; Penton-Voak et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we were primarily interested in studying the online effects of induced awe on temporal judgments (i.e., while participants were actually engaged in watching the aweeliciting movies), we used a bisection task while participants were watching the different videos. Specifically we used a tactile bisection task (Jia, Shi, Zang, & Muller, 2015;Shi, Jia, & Muller, 2012), in which participants categorized vibrotactile stimuli as being of short or long duration. The advantage of this task is that it does not interfere with the other sensory modalities (i.e., vision and sound) that are used to elicit awe to prevent any interference.…”
Section: Introductionmentioning
confidence: 99%